City and society in the Low Countries, 1100-1600 - Blondé, Bruno, 1964-; Boone, Marc, 1955-; Van Bruaene, Anne-Laure, 1975- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2018)
"The Low Countries was collectively one of the earliest and most heavily urbanised societies in European history. Present-day Belgium and the Netherlands still share important common features, such as comparatively low income inequalities, high levels of per capita income, a balanced political structure, and a strong 'civil society'. This book traces the origins of this specific social model in medieval patterns of urbanisation, while also searching for explanations for the historical reproduction of social inequalities"--
City and society in the Low Countries: urbanisation and urban historiography / Bruno Blondé, Marc Boone & Anne-Laure Van Bruaene -- Economic vitality: urbanisation, regional complementarity and European interaction / Wim Blockmans, Bert De Munck & Peter Stabel -- Living together in the city: social relationships between norm and practice / Bruno Blondé, Frederik Buylaert, Jan Dumolyn, Jord Hanus & Peter Stabel -- "The common good": governance, discipline and political culture / Marc Boone & Jelle Haemers -- Civic religion: community, identity and religious transformation / Guido Marnef & Anne-Laure Van Bruaene -- Urban space: infrastructure, technology and power / Claire Billen & Chloé Deligne -- At home in the city: the dynamics of material culture / Inneke Baatsen, Bruno Blondé, Julie De Groot & Isis Sturtewagen -- Education and knowledge: theory and practice in an urban context / Bert De Munck & Hilde De Ridder-Symoens -- Epilogue: the legacy of the medieval city in the Low Countries / Bruno Blondé, Marc Boone & Anne-Laure van Bruaene.
"Originally published in Dutch by Academia Press 2016 as Gouden eeuwen: Stad en samenleving in de Lage Landen, 1100-1600."
Includes bibliographical references and index.
Keywords: Urbanization -- History -- Belgium; Urbanization -- History -- Netherlands